Pengaruh Penggunaan Bahasa Gaul Dalam Interaksi Mahasiswa : Studi Kualitatif Tentang Penggunaan Bahasa Gaul Dikalangan Mahasiswa IKM UINSU - Usiono Usiono; Nesa Ariska; Aisha Nurul Azkia; Nur Azizah Chairuna Balqis Tanjung (Universitas Maritim AMNI Semarang, 2025)
This research aims to explore more deeply the phenomenon of slang use among UINSU Public Health students and its impact on social dynamics and the development of their identity. Through a qualitative approach involving in-depth interviews and participant observation, this research seeks to understand how slang plays a role in forming social bonds, creating a sense of belonging to a group, and influencing the way students interact with each other. Preliminary findings show that slang not only functions as a communication tool, but also as a symbol of identity and a means of expressing oneself. However, on the other hand, the use of slang that is too intense can blur the boundaries between formality and informality, thus potentially hampering the learning process and effective academic communication. Therefore, this research highlights the importance of balancing the use of slang with good and correct language rules, so that students can communicate effectively in various contexts without sacrificing their group identity.